Risk management in Belum Rainforest Resort: a case study / Nur Rahifah Amirudin - Amirudin, Nur Rahifah (2012)
In today's world, the relationship between risk and business performance is undeniable. Every business venture proved to be risky, regardless the size and type of business. The riskiness of the business has prompted the management to find ways to manage the risks to an accepted level. Risks can be classified into several forms and it may derive from many sources. The purpose of this applied research is to identify the type of risks that associate with the operation of the resort. This study will look into the factors that contribute to the occurrence of risk. Those factors could derive from the internal or external environment. The impact of risks to the performance of the resort, either financial or non financial will be given the same attention. This study also examines the effectiveness of the risk management process implemented in resort. In order to examine the type of risk faced by the resort, the factor and impacts of risk, a case study of Belum Rainforest Resort is chosen. Finally, the conclusion of this study shows the risks can be managed through the right combination of risk management techniques. Some recommendation has been made to increase the effectiveness of the risk management process implemented in Belum Rainforest Resort.